Structural and Dielectric Properties of Mn Doped SnO2 Prepared by Solid State Reaction - Mahmood, Sara S.; Hasan, Bushra A.; Rauuf, Aws F.; Hasan, Ahmad A. (Iraqi Journal of Science, 2025)
This study shows how the structural and dielectric properties of (SnO2)1-x(Mn2O3)x, (where x=0.00, 0.03, 0.05,0.07, and 0.09) prepared using the solid state reaction technique, are affected by the doping of semiconducting metal oxide Mn2O3. Structural analysis of the composites was carried out using information from the composite samples obtained from X-ray diffraction (XRD). The diffraction peak shifting in XRD patterns indicated that Mn ions were successfully incorporated into the SnO2 crystal lattice. Mn ions were successfully doped in the Tin oxide matrix lattice with the subsequent increase of doping levels. The average crystal size evaluated using Scherrer’s equation was found to vary from 33 to 37 nm, and the lattice constants were a=4.68-3.69 and c=3.166-3.173. This work also tested the dielectric characteristics of (SnO2)1-x(Mn2O3) x composites. The effects of Mn doping were interpreted and discussed. The effects of Mn doping on the σa.c(ω), exponent (s), dielectric constant, dielectric loss, relaxation time, and polarizability were also studied.